1178 RETROSPECTIVE SURVEY OF DIFFERENTIAL DIAGNOSES IN A NEUROVASCULAR CLINIC. (16th January 2023) - Awatramani, S; Kulendran, A; Umasankar, U; Patel, M
Abstract: Introduction: Diagnosis of Transient Ischaemic Attack [TIA] is important to minimise risk of future strokes. This retrospective descriptive study aimed to describe frequency of alternative diagnoses in a busy inner-city neurovascular clinic and evaluate processes of assessment and investigations of 'true' TIA patients. Methods: Data was obtained over a 2-year period [2019-2020] for all new patients assessed in a busy consultant-provided daily week-day neurovascular service that serves a million multi-ethnic, population. Data collected included socio-demographic details, final clinical diagnoses, and process measures including speed of assessment and rate of neurological and cardiological investigations. Results: Of 1764 patients, 39.3%[694] were diagnosed as TIA; 60.7%[1070] had 40 distinct differential diagnoses. Top ten diagnoses included migraine including ocular migraine [9.5%], Syncope [5.5%], Local Eye conditions (non-neurological)[5.3%], non-cervical radiculopathy [4.0%], Benign Paroxysmal Positional Vertigo [4.0%], Previous/Incidental Stroke [3.7%], Transient Global Amnesia [2.4%], Orthostatic Hypotension [1.8%], Non-migraine Headache syndromes [1.6%], Cervical Neuropathy [1.3%]. 10.9%[193] had no organic pathological diagnosis. For 694 TIA patients, 100% had neuroimaging [CT/MRI] and 98% had carotid dopplers on or before day of clinic. Non-urgent cardiovascular investigations performed included echocardiogram [83%], Holter monitoring [75%] and bubble echocardiogram [5%]. Discussion: This large survey has described the frequency of TIA and alternative diagnoses in a dedicated neurovascular service. The study highlights the importance of accurate diagnosis of TIA by experienced clinicians for appropriate secondary prevention. We also described the efficiency, and speed of assessment and proportion of investigations undertaken in these patients. This study provides valuable information to clinicians, researchers and commissioners of stroke services in future.